Analisis Determinan Pelaporan Islamic Social Reporting (ISR) Pada Bank Umum Syariah Indonesia Tahun 2015-2019 - Rozzi, Muhammad Fathur; Bahjatullah, Qi Mangku (MALIA: Journal of Islamic Banking and Finance, 2020)
This study aims to determine how the influence of Profitability (GPM), Liquidity (CR), and Leverage (DER) on Islamic Social Reporting (ISR) with Company Size as a Moderating Variable, in Islamic Commercial Banks in Indonesia which are registered with the OJK for the 2015-2019 period. This research uses quantitative research, type with secondary data in the form of panels analyzed through multiple linear regression data analysis method with Moderate Regression Analysis (MRA) test using EViews 9 software. The population used in this research is Islamic Commercial Banks (BUS) in Indonesia as many as 14 Islamic banks. The sampling technique in this study was purposive sampling. The sample used as the research object was 12 BUS. Based on the results of the study, the F-test results show that Profitability, Liquidity and Leverage simultaneously affect the ISR with a positive coefficient while the T-test shows that partially Profitability and Leverage have no effect on ISR, Liquidity has a negative and significant effect on ISR. Based on the MRA test, Company Size is unable to moderate the relationship between the effect of profitability on ISR, while Company Size is able to moderate and weaken the relationship between Liquidity and ISR, and Company Size is able to moderate and strengthen the relationship between Leverage and ISR.